2022
DOI: 10.3390/ijerph19031340
|View full text |Cite
|
Sign up to set email alerts
|

Input-Output Efficiency of Water-Energy-Food and Its Driving Forces: Spatial-Temporal Heterogeneity of Yangtze River Economic Belt, China

Abstract: The high-quality development of the Yangtze River Economic Belt (YREB) plays a crucial role in economic transformation in China. Climate change, rapid population growth, and increased urbanization have contributed towards increased pressures on the water, energy, food (WEF) nexus system of YREB. Thus, there is an imperative need to improve the efficiency of WEF in YREB. However, few studies have conducted spatial-temporal heterogeneity exploration of YREB about the input-output efficiency of WEF (IOE-WEF). Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Among them, the regions involved in the Yangtze River Economic Belt also show a similar efficiency ranking and indicate the trend that the efficiency of eastern coastal areas is higher than that in the western inland areas of the Yangtze River Economic. Ge et al (2022) concluded that the input-output efficiency of WEF nexus of Sichuan, Hubei, Hunan, and Jiangxi has decreased, which is basically consistent with the results of this study. Compared with the existing relevant literature, this study starts from the spatial elements, analyzes the spatial distribution and change trend of efficiency, and puts forward two new indicators to enrich the research content from the spatial perspective.…”
Section: Discussionsupporting
confidence: 91%
“…Among them, the regions involved in the Yangtze River Economic Belt also show a similar efficiency ranking and indicate the trend that the efficiency of eastern coastal areas is higher than that in the western inland areas of the Yangtze River Economic. Ge et al (2022) concluded that the input-output efficiency of WEF nexus of Sichuan, Hubei, Hunan, and Jiangxi has decreased, which is basically consistent with the results of this study. Compared with the existing relevant literature, this study starts from the spatial elements, analyzes the spatial distribution and change trend of efficiency, and puts forward two new indicators to enrich the research content from the spatial perspective.…”
Section: Discussionsupporting
confidence: 91%
“…Meanwhile, transform the comparative advantages of less efficient areas, enhance the absorptive capacity of adjacent areas with high governance efficiency, use environmental regulatory policies to limit the "bad performance" of less efficient areas in terms of water use efficiency and total carbon emissions (Ge et al, 2022), and compel the central government to speed up the elimination of non-ecological production capacities, promote the upgrading of the old industrial structure, form the "birdcage" model of efficient development, and transform the high-cost, lowefficiency model of development to a model which considers both ecological and economic efficiency.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Several other theories used in publications based on the findings in this study include the Inputoutput system theory theory as many as 2 publications. This theory is used by (53)in his research on input-output efficiency of water-energy-food in the study of spatial-temporal heterogeneity in the Yangtze river in China. The same theory was used in research (26)to evaluate the economic, environmental and social impacts of the COVID-19 pandemic on the tourism industry in Japan.…”
Section: Classification Based On Theoretical Frameworkmentioning
confidence: 99%
“…In his study, Kitamura measured tourism consumption during Covid 19 in Japan, the Carbon Footprint (CFP) and employment related to the impact of the Covid 19 pandemic. Furthermore, research (53)regarding the efficiency of input-output from water-energy-food and The driving forces on China's Yangtze River against a backdrop of climate change, China's rapid population growth, and increasing urbanization have contributed recently to increasing pressure on the water-energy-food nexus system in China's Yangtze River economic belt.…”
Section: Classification Based On Research Contextmentioning
confidence: 99%